Food restriction during pregnancy and female offspring fertility: adverse effects of reprogrammed reproductive lifespan - Abdel Halim Harrath; Abdulkarem Alrezaki; Lamjed Mansour; Saleh H. Alwasel; Stefano Palomba (BMC, 2017)
Abstract Background Food restriction during pregnancy can influence the health of the offspring during the adulthood. The aim of the present study was to examine the effect of maternal food restriction (MFR) on the reproductive performance in female rat offspring from the first (FR1) and second (FR2) generations. Methods Adult virgin Wistar female rats were given free access to tap water and were fed ad libitum on standard rodent chow, were mated with virgin adult males, and then were randomly divided into two groups: controls (that was fed ad libitum ) and food-restricted group (FR, that was given only 50% of ad libitum food throughout gestation). Their first (FR1) and the second (FR2) generation of offspring were fed ad libitum and sacrificed before puberty and at adulthood. Their ovaries were removed and their histology evaluated by estimating the number of follicles (total and at various stages of folliculogenesis), and the presence of multi-nuclei oocytes and multi-oocyte follicles. Results Total number of ovarian follicles was lower in FR1 females at week 4 in comparison with controls, while it was not different in FR2 females vs. controls. The number of the primordial follicle was lower in FR1 and FR2 females vs. controls at both week 4 and at week 8. When compared to the controls, the follicles containing multi-nuclei oocytes were more frequent in ovaries from FR1 and FR2 females at week 4, and higher and lower respectively in ovaries form FR1 and FR2 females at week 8. Conclusion MFR affects ovarian histology by inducing the development of abnormal follicles in the ovaries in first and second generation offspring. This finding could influence the ovarian function resulting in an early pubertal onset and an early decline in reproductive lifespan.